ANALISIS PENDOKUMENTASIAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA BERDASARKAN PP NO. 50 TAHUN 2012 DI PT ANGKASA PURA II (PERSERO) BANDUNG - Yuliani, Novi; Ekawati, Ekawati; Kurniawan, Bina (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Occupational Health And Safety Management System or called OHSMS is a part of company management system in order to risk control that associated with work process to make a safe and healthy workplace. In PP No. 50 Tahun 2012 requires to documenting all important element in OHSMS and everything that associated with those element. PT Angkasa Pura II (Persero) Bandung have applying OHSMS for 1 year since March 2014 and already certified but in implementation at the workplace especially in documentation of OHSMS, there are still many documents related to the implementation OHSMS have not been made by worker, because the safety unit has not establish in this company.The purpose of this research was to analyse compatibility of documenting OHSMS with the regulation. This research is a descriptive qualitative research with indepth interview. The subjects of this research were 4 people as key informants from worker of every unit, Teknik Umum, TLMP, PKP-PK and Elektronika and 1 people as a triangulation informant is OHS coordinator. The result show there is still mismatch of OHSMS reporting based on the government regulation. Controlling document done with structuring and maintenance the documents. Recording and information management held for workers with socialization and for guest or others through OHS Coordinator. This needs socialization and training about OHSMS. Procedure of reporting system, forming an OHS unit and procurement information boards about OHS.